2023
DOI: 10.1002/batt.202300080
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Limitations of Research Battery Cell Types for Electrochemical Data Acquisition

Abstract: Developing new electrode materials and/or electrolytes for lithium‐ion batteries requires reliable electrochemical testing thereof. For this purpose, in academic research typically hand‐made coin‐type cells are assembled. Their advantage is a rather cheap and facile assembly, and possibility to prepare full‐cells as well as half‐cells, meaning cathode‐anode or electrode‐elemental lithium configurations. Critical parameters for testing data quality and the potential and limitations of cell tests in half‐cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…To calculate the precise N/P ratio later on, electrodes were weighted prior to their use. It has recently been shown that the steel grade of coin cell cases can have an enormous impact on the cycle life of alkali-ion batteries cycled vs. carbon-based anodes [23] and accordingly, coin cell parts made of S316L steel were chosen. After crimping, the cells were cleaned to remove any electrolyte deposits and possible salt bridges.…”
Section: Full-cell Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…To calculate the precise N/P ratio later on, electrodes were weighted prior to their use. It has recently been shown that the steel grade of coin cell cases can have an enormous impact on the cycle life of alkali-ion batteries cycled vs. carbon-based anodes [23] and accordingly, coin cell parts made of S316L steel were chosen. After crimping, the cells were cleaned to remove any electrolyte deposits and possible salt bridges.…”
Section: Full-cell Testsmentioning
confidence: 99%
“…All results were achieved in coin cells, which are known to have reduced lifetimes compared to pouch cells. [23] It can therefore be assumed that the degradation can still be significantly reduced by changing the cell format and that an excellent cycling stability should be possible based on NVP/C vs. HC cells with NaPF 6 in EC/PC as electrolyte. Likewise, it becomes evident that FEC, which doubtlessly extends the lifetime of NVP vs. Na cells, [30] reduces the lifetime of NVP vs. HC cells and is therefore not a suitable additive in full-cells.…”
Section: Cycling Stability Test and Internal Resistancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the quality of the assembly process and parts used in coin cell preparation can greatly affect the representativeness and reproducibility of the electrochemical results. [1][2][3] Thus, academic researchers have increasingly adopted highly reproducible, industrial-quality wound pouch cells for more accurate studies. [4][5][6][7] However, these wound pouch cells are not always practical, especially for novel active material evaluation because they require larger amounts of material than typically synthesized at laboratory-scale.…”
mentioning
confidence: 99%